2008
DOI: 10.1371/journal.pcbi.1000140
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Hubs in the Yeast Protein Interaction Network Tend To Be Essential: Reexamining the Connection between the Network Topology and Essentiality

Abstract: The centrality-lethality rule, which notes that high-degree nodes in a protein interaction network tend to correspond to proteins that are essential, suggests that the topological prominence of a protein in a protein interaction network may be a good predictor of its biological importance. Even though the correlation between degree and essentiality was confirmed by many independent studies, the reason for this correlation remains illusive. Several hypotheses about putative connections between essentiality of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
313
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(333 citation statements)
references
References 36 publications
19
313
1
Order By: Relevance
“…Furthermore, to account for gene dosage imbalances (22, 23), we also removed (i) all of the ribosomal proteins or (ii) all known protein complexes and found that our conclusions are still robust (S1.7 and test 6, P < 2.2e −9 , Wilcoxon's test; and S1.7 and test 7, P < 9.8 e −7 , Wilcoxon's test, respectively). We also controlled for potential biases arising from (i) differences in protein abundance (24) (S1.8 and test 8; P < 3.3 e −5 , Wilcoxon's test), (ii) coverage (S1.8 and test 9; P = 0.009, Wilcoxon's test) in the various experiments, (iii) essentiality of genes (25-29) (S1.8 and test 10; P < 2.3e −6 , Wilcoxon's test), or (iv) protein interaction network centrality (27,29,30) (S1.8 and test 11; P < 3e −7 , Wilcoxon's test) and still found that WGD proteins contained more p-sites. The importance of taking into consideration protein function in evolutionary analyses as performed here has been highlighted previously (31).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, to account for gene dosage imbalances (22, 23), we also removed (i) all of the ribosomal proteins or (ii) all known protein complexes and found that our conclusions are still robust (S1.7 and test 6, P < 2.2e −9 , Wilcoxon's test; and S1.7 and test 7, P < 9.8 e −7 , Wilcoxon's test, respectively). We also controlled for potential biases arising from (i) differences in protein abundance (24) (S1.8 and test 8; P < 3.3 e −5 , Wilcoxon's test), (ii) coverage (S1.8 and test 9; P = 0.009, Wilcoxon's test) in the various experiments, (iii) essentiality of genes (25-29) (S1.8 and test 10; P < 2.3e −6 , Wilcoxon's test), or (iv) protein interaction network centrality (27,29,30) (S1.8 and test 11; P < 3e −7 , Wilcoxon's test) and still found that WGD proteins contained more p-sites. The importance of taking into consideration protein function in evolutionary analyses as performed here has been highlighted previously (31).…”
Section: Resultsmentioning
confidence: 99%
“…The subgraph centrality has been previously applied to the identification of essential proteins in proteomic maps (Estrada, 2006a;2006b;Zotenko et al, 2008;Lin et al, 2008;Gursoy et al, 2008) and the characterization of malignant tissues (Platzer et al, 2007). It has also been applied to the study of weighted graphs to account for the degree of folding of protein chains (see for instance Estrada, 2002;2004) as well as to describe the molecular structure of drug-like and environmentally relevant organic compounds (for a review see Estrada and Uriarte, 2001).…”
Section: Study Of Protein-protein Interaction Networkmentioning
confidence: 99%
“…For instance, the so-called centrality-lethality rule was first suggested by Jeong et al (3) and Yu et al (4), stating that highly connected proteins tend to be essential. Furthermore, such hubs are also involved in a rising number of protein complexes (5), suggesting that their essentiality is a consequence of their complex involvement (6,7). In humans, human viruses and parasites target certain proteins to seize control of a host cell (8,9) whereas such proteins play a decisive role in different cancer types (10,11).…”
mentioning
confidence: 99%